Imaging the fetal aortic arch and its branching pattern in a mid-trimester screening population - Tavares de Sousa, Manuela; Hergert, Bettina; Crispi, Fatima; Gomez, Olga; Hecher, Kurt (Ultraschall in der Medizin - European Journal of Ultrasound, 2025)
Aortic arch branching variants have recently been found to have an impact in neonates undergoing surgical interventions involving the thoracic aorta such as aortic coarctation repair. They have been described prenatally in 6% of neonates, whereas they occur in up to 26% postnatally. To explore whether the branching variations might have been underdiagnosed in utero, we comprehensively assessed the aortic arch and its branching patterns in a low-risk population between the 19th and 22nd week of gestation.This prospective cohort study included 139 low-risk singleton pregnancies. During a standardized fetal echocardiography examination, we investigated the aortic arch in a sagittal view according to predefined landmarks. Based on video clips, its branching pattern was categorized as normal branching or branching variants by 2 operators who were blinded to each other.Classification of aortic arch branching was achieved in 127/139 cases (91.4%). 103 cases (81.1%) showed a normal pattern, and 24 cases (18.9%) showed a branching variant. Both operators agreed on 18 brachiobicephalic trunks (the so-called bovine arch), 4 aberrant left vertebral arteries, 1 aortic arch with 5 branching vessels. In 1 case there was disagreement regarding the type of variant.Prenatal targeted echocardiography could identify 18.9% prevalence of aortic arch branching variants in a low-risk population. Future studies are warranted to assess the clinical impact of our findings on neonates with congenital heart defects.
Keywords: aortic arch branching; bovine aortic arch; brachiobicephalic trunk; fetal aortic arch; aortic arch variants